2014
DOI: 10.1021/jp5049716
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Stability of Cations in Ionic Liquids. 5. Task-Specific Ionic Liquids Consisting of Biocompatible Cations and the Puzzle of Radiation Hypersensitivity

Abstract: In 1953, an accidental discovery by Melvin Calvin and co-workers provided the first example of a solid (the α-polymorph of choline chloride) showing hypersensitivity to ionizing radiation: under certain conditions, the radiolytic yield of decomposition approached 5 × 10(4) per 100 eV (which is 4 orders of magnitude greater than usual values), suggesting an uncommonly efficient radiation-induced chain reaction. Twenty years later, the still-accepted mechanism for this rare condition was suggested by Martyn Symo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 119 publications
0
9
0
Order By: Relevance
“…Conversely, the acetaldehyde C==O stretch at 1733 cm −1 (ε = 189 M −1 cm −1 ) can be easily resolved from the IL background absorption. 21 Based on the observed kinetics, our results suggested that most of the radiolytically induced C 1 -N fragmentation in choline NTf 2 occurs promptly (within 40 ns), and that there is a further ∼40% increase in the yield of vinyl alcohol over the following 400 µs. These results, combined with other data using different techniques, led to a revision of the previously accepted Symons mechanism of radiation hypersensitivity in choline chloride and a demonstration that the conditions that lead to hypersensitivity do not exist in ILs.…”
Section: A Previous Investigationsmentioning
confidence: 68%
See 3 more Smart Citations
“…Conversely, the acetaldehyde C==O stretch at 1733 cm −1 (ε = 189 M −1 cm −1 ) can be easily resolved from the IL background absorption. 21 Based on the observed kinetics, our results suggested that most of the radiolytically induced C 1 -N fragmentation in choline NTf 2 occurs promptly (within 40 ns), and that there is a further ∼40% increase in the yield of vinyl alcohol over the following 400 µs. These results, combined with other data using different techniques, led to a revision of the previously accepted Symons mechanism of radiation hypersensitivity in choline chloride and a demonstration that the conditions that lead to hypersensitivity do not exist in ILs.…”
Section: A Previous Investigationsmentioning
confidence: 68%
“…One example of this is our recent investigation of the mechanism of radiolytic decomposition of a choline-based ionic liquid (IL) in collaboration with Dr. Ilya Shkrob of Argonne National Laboratory. 21 There is great interest in ILs and deep eutectic mixtures that are based on choline ((2-hydroxymethyl)trimethylammonium), betainium (1-carboxy-N,N,N-trimethylmethanaminium), and other derivatized natural amino compounds as diluents in metal ion separations, 33 including nuclear separations where the constituent ions would be exposed to ionizing radiation that is emitted by decaying radionuclides. 34 Thus, it is critical to investigate the radiation stability of such ILs, particularly since they are compositionally similar to radiation hypersensitive solids such as choline chloride, which decomposes significantly upon irradiation.…”
Section: A Previous Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hole-eliminated transient absorption spectrum of the solvated electron is thus solely represented by curve c of Figure A. The solvated electron in the IL, bearing a choline cation (NTf 2 anion) at 45 °C, shows a peak in the wavelength range of 630–650 nm in its absorption spectrum, close to that in alcohols and ILs containing alcohol-substituted ammonium cations . The solvated electron absorption peak in reline is thus red-shifted to 760 nm as compared to that in choline-NTf 2 .…”
Section: Resultsmentioning
confidence: 97%